Species of Euglossa of the analis group in the Atlantic forest (Hymenoptera, Apidae) - Faria,Luiz R. R. (2012)
The species of Euglossa Latreille, 1802 of the analis group inhabiting the Brazilian Atlantic forest are revised and identification keys for males and females are provided. Five species are recognized in the Atlantic forest: Euglossa cognata Moure, 1970, Euglossa marianae Nemésio, 2011, Euglossa roderici Nemésio, 2009 and two new species described here, Euglossa botocuda sp. nov. and Euglossa calycina sp. nov. These two new species have been misidentified by previous authors as Atlantic forest populations of, respectively, Euglossa iopyrrha Dressler, 1982 and Euglossa mixta Friese, 1899. Relevant morphological features are illustrated and distribution maps are also provided. Notes on the analis group are included and an additional available name, Euglossa aureiventris Friese, 1899, is placed in this species group.